Been a heavy life : stories of violent men - Presser, Lois (Critical perspectives in criminology., 2008)
Investigates the life stories of men who have perpetrated violence. Presser applies insights from across the academy to in-depth interviews with men who shared their accounts of how they became the people we most fear--those who rape, murder, assault, and rob, often repeatedly. She provides the discipline of criminology with two crucial frameworks: one for critically evaluating the construction of offenders' own stories, and one for grasping the cultural meta-narratives that legitimize violence. From publisher description.